Determination of genetic relatedness of selected individual trees of Shorea leprosula Miq. and Dipterocarpus cornutus Dyer in forest seed production areas - Wickneswari, Ratnam; Ho, Seng (The Japan Society of Tropical Ecology, 2003)
The genetic relatedness of selected mother trees of Shorea leprosula (24 trees) and Dipterocarpus cornutus (10 trees) was investigated using four simple sequence repeats (SSRs) loci in two seed production areas, a 1 ha seed stand of S. leprosula and a 0.9 ha seed stand of D. cornutus in Compartment 17, Labis Forest Reserve, Segamat, Johor. A total of 24 and 32 saplings in the vicinity of selected mother trees of S. leprosula and D. cornutus, respectively was collected for parentage analysis. Based on SSR polymorphisms, four ...